2022
DOI: 10.1016/j.imed.2021.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Social media study of public opinions on potential COVID-19 vaccines: informing dissent, disparities, and dissemination

Abstract: Background: The current development of vaccines for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is unprecedented. Little is known, however, about the nuanced public opinions on the vaccines on social media. Methods: We adopt a human-guided machine learning framework using more than six million tweets from almost two million unique Twitter users to capture public opinions on the vaccines for SARS-CoV-2, classifying them into three groups: pro-vaccine, vaccine-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 36 publications
0
20
0
Order By: Relevance
“…The reason why we chose these 2 attributes is that account age can reflect the internet age of a user, and follower number can indicate a user’s influence and usage level of social media to a certain extent. Additionally, Lyu et al [ 31 ] studied the characterization of population groups with varied attitudes toward COVID-19 vaccines and concluded that account age and follower number also have an influence on population attitudes toward vaccines. The account age of a user was calculated by subtracting the user’s creation time from the tweet’s creation time, and the follower number was retrieved directly from the “stats” field of the tweet object.…”
Section: Methodsmentioning
confidence: 99%
“…The reason why we chose these 2 attributes is that account age can reflect the internet age of a user, and follower number can indicate a user’s influence and usage level of social media to a certain extent. Additionally, Lyu et al [ 31 ] studied the characterization of population groups with varied attitudes toward COVID-19 vaccines and concluded that account age and follower number also have an influence on population attitudes toward vaccines. The account age of a user was calculated by subtracting the user’s creation time from the tweet’s creation time, and the follower number was retrieved directly from the “stats” field of the tweet object.…”
Section: Methodsmentioning
confidence: 99%
“…Lastly, regardless of the setup of the county mass sites and FEMA site prioritizing accessibility for populations disproportionately affected by the pandemic, there is still disparity in vaccination rate among populations and communities. Our study only focused on accessibility to vaccine resources and did not consider one major factor that influences vaccination rates, which is vaccine acceptance/hesitancy ( 36 39 ). More in-depth studies on this front could provide valuable insights to innovative solutions in mass vaccination campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…We hope that our findings will encourage the deployment of other mobile facilities, employing similar infection control measures to minimize the risk to patients and healthcare workers within the mobile facility. We further hope that the Smart Pod will allow for easier access and a novel approach to COVID-19 vaccine delivery, especially in underserved communities with higher rates of vaccine hesitancy [50].…”
Section: Discussionmentioning
confidence: 99%